Uniqueness of Meromorphic Functions When Two Differential Polynomials Share One Value - Banerjee, Abhijit; Sahoo, Pulak (Sarajevo Journal of Mathematics, 2024)
The paper deals with the uniqueness problems of meromorphic functions related to differential polynomials that share one value with finite weight. We prove three uniqueness results which significantly rectify, improve and supplement some recent results of [6] and [6b]. 2000 Mathematics Subject Classification. 30D35